IMPLEMENTATION OF STEM PROJECT BASED LEARNING TO INCREASE SCIENTIFIC WORK SKILLS OF PROSPECTIVE STUDENTS OF PRIMARY SCHOOL TEACHER - Arfilia Wijayanti; Khusnul Fajriyah (Pendidikan Kimia Unimus, 2018)
This study aims to determine the improvement of scientific work skills of prospective students of primary school teachers after implemented by STEM Project Based Learning. This research is designed with pre experiment method with one shot case study design, that is sample consist of one experimental class that get a treatment, that is implements STEM Project Based Learning in science lecture at grade of teacher candidate of SD PGSD FIP UPGRIS Semarang. Based on the results of N-Gain analysis, the data obtained obtained the improvement of the scientific work skills of prospective teachers of SD Prodi PGSD FIP UPGRIS by 0.8 in the classical or in the high category of improvement. Improvement of scientific work skills per indicator from the highest to the lowest ie communication and interpretation skill, planning the experiments skill that each get the value of N-Gain 0.9 ie in the high category, the classification gets value of N-Gain 0.8 ie in the high category, the observation skill get the value of N-Gain 0.7 is on the high category, and ask questions skill get the value 0.5 that is in the category of being. It was concluded that the implementation of STEM Project Based Learning could improve the scientific work skills of prospective elementary school teachers.